IDA-PBC Control of an Underactuated Underwater Vehicle - Diego García; Jesús Sandoval; Joaquín Gutiérrez–Jagüey; Eusebio Bugarin (Revista Iberoamericana de Automática e Informática Industrial RIAI)
This paper presents an IDA-PBC (Interconnection and Damping Assignment-Passivity Based Control) for underactuated undewater vehicle control, which it has more degree of freedom than actuators. In this proposal, six degree of freedom and only four propels as actuators are considered, which it oers a main control challenge. Specifically, the IDA-PBC proposed drives the vehicle towards a desired deep and orientation. Simulation results on a vehicle model validate the performance of the control scheme proposed.